Elements of the visual structure in contemporary television drama The Turkish series Hareem Al-Sultan, the first part, as a model ( An analytical study ) (Journal of the College of Basic Education, 2022)
Mirror image of thought in psychology as (gold Sheikh President Ibn Sina that the divine self-actor creates images and concepts in the mind College) is gliding through the sensuous, which consists of diverse material. Including images kinetic in TV drama and it teleological , called the image dramas, which are distinctive types, each type elements own, and these elements are that specifies the thought and skill own for the employees and also the type of technology and the extent of Contemporary and interaction for the present and their interaction with science, for the reasons urgent that appeared by the image of the Turkish series Harem Sultan with a high degree of dazzling, deliberately researcher to study the elements of this image-building and stand on the type and pattern of stylistic and established aesthetic reactive with contemporary philosophy of science and art. Search came in four chapters, the first chapter research problem and importance of , the need for , objectives of its borders , its terminology. Chapter II consisted of three Detectives , first date philosophical concept's motor - dramas, The second strength construction image drama - built and the determinants of the backs, The third image properties dramatic Television contemporary, and indicators of the theoretical framework and previous studies, while the third contained a search procedures represented in the sample and the methodology of analysis fourth and discuss the results, and then the list of sources and photographers sources.